The Identification of Wotu People’s Local Wisdom Values and Their Role in Indigenous Parenting - Yusuf, Nur Mawakhira; Masri, Subekti; Kasmi, Kasmi; Ali, Salmiati; Ilahi, Ais Nur; Dress, Gunther (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Indigenous parenting is a parental attitude towards children that creates an emotional experience for children based on their cultural values. This research was conducted to find out the value of local wisdom that is still maintained in the life of the Wotu community in indigenous parenting. This research is a qualitative research based on data obtained in the field using observation, interview and documentation methods. The results showed that there are several parenting cultures that exist in the Wotu community related to the identification of local wisdom values of the community and their role in indigenous parenting, namely awa itaba la awai assangoatta, lalembata tarantajo, and sinunu isinunui which have an important role in family or social relationships that exist in the Wotu community. The results of this study contribute to the traditional parenting of communities that embrace local wisdom values in shaping the emotional climate between parents and children amid the influence of modernising culture.